Kekuatan Hukum Akta Jual Beli Tanah yang Dibuat PPAT (Studi Kasus Putusan Kasasi MA No. 787 K/Pdt/2013) - Sigit Dwi Santoso (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
Land issues are an issue that always arises and always actual from time to time. One of the land issues is a land dispute case that occurred in Sleman district, which has been examined and issued a decision on appeal with Supreme Court verdict. 787 K/Pdt/2013 on December 17, 2013, of which one of its decisions is "to declare invalid and null and void in The Deed of Sale and Purchase Number 141/2004 dated November 26, 2004". Surely this raises legal issues, in the form of "the existence of The Deed of Sale and Purchase made by PPAT which is an authentic deed". At the end of this paper, two things are concluded. Firstly, the existence of this verdict has indicated the existence of legal protection, in the form of: declaring invalid and void according to the law of the sale and purchase of the land because it is not in accordance with customary law, which is cash, light, and real. Secondly, the existence of this verdict has indicated the existence of legal certainty, by declaring invalid and null and void of the Deed of Sale and Purchase of Land made by PPAT.